Germs : biological weapons and America's secret war - Miller, Judith, 1948-; Engelberg, Stephen, 1958-; Broad, William J. (New York : Simon & Schuster, 2001)
"Deadly germs sprayed in shopping malls, bomblets spewing anthrax spores over battlefields, tiny vials of plague scattered in Times Square - these are the poor man's hydrogen bombs, hideous weapons of mass destruction that can be made in a simple laboratory." "In this work of investigative journalism, Judith Miller, Stephen Engelberg, and William Broad of The New York Times uncover the truth about biological weapons and show why bio-warfare and bio-terrorism are fast becoming our worst national nightmare." "Germs also shows how a small group of scientists and senior officials persuaded President Bill Clinton to launch a controversial multibillion-dollar program to detect a germ attack on U.S. soil and to aid its victims - a program that, so far, is struggling to provide real protection." "Based on hundreds of interviews with scientists and senior officials, including President Clinton, as well as on recently declassified documents and on-site reporting from the former Soviet Union's sinister bio-weapons labs, Germs shows us bio-warriors past and present at work at their trade. There is the American scientist who devoted his professional life to perfecting biological weapons, and the Nobel laureate who helped pioneer the new biology of genetically modified germs and is now trying to stop its misuse. We meet former Soviet scientists who made enough plague, smallpox, and anthrax to kill everyone on Earth and whose expertise is now in great demand by terrorists, rogue states, and legitimate research labs alike."--BOOK JACKET.
Attack -- Warrior -- Revelations -- Saddam -- Secrets and lies -- Cult -- Evil empire -- Breakthrough -- Taking charge -- President -- Defenders -- Future.
Includes bibliographical references (p. 364-367) and index.
Keywords: Biological warfare -- United States -- Safety measures; Biological warfare -- Research -- United States; Biological warfare -- United States; Biological warfare -- prevention & control -- United States; USA; Biological warfare-Safety measures-United States; Biological warfare-Research-United States